2019
DOI: 10.7717/peerj.8155
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA detection and quantification of invasive red-eared sliders,Trachemy scripta elegans, in ponds and the influence of water quality

Abstract: Environmental DNA (eDNA) is a powerful tool for monitoring the distribution of aquatic macro-organisms. However, environmental factors, including the water temperature and water quality, can affect the inhibition and/or degradation of eDNA, which complicates accurate estimations of eDNA concentrations and the detection of the presence/absence of species in natural habitats. Further very few eDNA studies have been conducted for reptiles, especially with respect to estimating their biomass and/or abundances. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Environmental DNA (eDNA) methods are innovative methods developed for monitoring macroorganisms, especially aquatic species (Ficetola et al, 2008;Minamoto et al, 2012;Taberlet et al, 2012;Takahara et al, 2012;Ushio et al, 2018;Kakuda et al, 2019;Tsuji et al, 2019). The eDNA method is used to investigate species distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental DNA (eDNA) methods are innovative methods developed for monitoring macroorganisms, especially aquatic species (Ficetola et al, 2008;Minamoto et al, 2012;Taberlet et al, 2012;Takahara et al, 2012;Ushio et al, 2018;Kakuda et al, 2019;Tsuji et al, 2019). The eDNA method is used to investigate species distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Most eDNA studies that use a filtration approach have been conducted in marine or freshwater systems, where water appears to be non-turbid at the time of collection [15][16][17][18]. This is owing to the unique set of challenges that turbid water poses when detecting eDNA, such as the clogging of filters and the presence of PCR inhibitors [19][20][21]. Previous studies have utilised extraction kits-which come with anti-inhibitory washes-various pore sizes, membrane types, and pre-filtration steps to prevent filter clogging [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Fediajevaite et al ( 2021 ) recognized that this may partially reflect research effort, as reptile studies were the second least represented in the meta‐analysis. Of the studies reviewed here, only 22% compared eDNA methods and traditional surveying (with temporal overlap between the two methods), with mixed results: three found eDNA and traditional survey detections were comparable (Akre et al, 2019 ; Kakuda et al, 2019 ; Kucherenko et al, 2018 ), three found eDNA outperformed traditional surveys (Feist et al, 2018 ; Matthias et al, 2021 ; Raemy & Ursenbacher, 2018 ), and two found that traditional surveys outperformed eDNA (Ratsch et al, 2020 ; Rose et al, 2019 ). These studies were not able to be directly compared to conclude whether eDNA outperforms traditional surveying due to substantial variation in sample methods, design, and reporting metrics.…”
Section: Integrating Edna and Other Survey Methodsmentioning
confidence: 95%